COVID 19 & THE LIFE OF THE CHURCH: THEOLOGICAL-ETHICAL CHALLENGES - Stanley, Sahayaraj (Asian Horizons, 2022)
Covid 19 was a game-changer in many ways. The life of the Church underwent tectonic shifts because of the challenges this pandemic posed. The Church as the body of Christ faced a real faith crisis. The fear of death loomed large and the very proximity of a human person became suspicious. We became prisoners of virtual reality but at the same time, we were forced to find God more in the digital space. Many of the faithful were glad to embrace the God of the gigabytes who quenched their spiritual thirst with voluminous online and offline reservoirs. The human person was forced to deal with the catastrophes of his own making and the global community became one in understanding the power of nature. The pandemic brought out the good Samaritan in all of us and the dedicated services of our healthcare personnel were lauded beyond measures. Though the fault lines of humanity are exposed, it is also time that we come together to work more in solidarity.